2017
DOI: 10.1111/soin.12186
|View full text |Cite
|
Sign up to set email alerts
|

The Universal King? Memory, Globalization, and Martin Luther King, Jr.

Abstract: This article examines how Martin Luther King, Jr. is remembered and represented by journalists in Ghana, South Africa, and Mexico, looking at coverage of “critical discourse moments” from King's life and legacy (1963–2016). I argue that representations of King vary in terms of local resonance—how well foreign figures or events align with local myths, values, and expectations—and global salience—the perceived world historical importance of a past figure or event. I then propose a new typology of global memory r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 53 publications
(84 reference statements)
0
4
0
Order By: Relevance
“…For example, Levy and Sznaider (2002) have shown that the Holocaust as a global memory has been rearticulated to inform discussions of universal moral values and to negotiate contemporary international conflicts. Other examples include the globalization of Martin Luther King Jr. as a figure of moral authority (Jijon, 2018) or the Rwandan genocide as a global memory of injustice (Olesen, 2012). Thus, global memories tend to be local events that are commemorated outside of national boundaries and get redefined in the process (A.…”
Section: Collective Memories Of the Globally Identifiedmentioning
confidence: 99%
“…For example, Levy and Sznaider (2002) have shown that the Holocaust as a global memory has been rearticulated to inform discussions of universal moral values and to negotiate contemporary international conflicts. Other examples include the globalization of Martin Luther King Jr. as a figure of moral authority (Jijon, 2018) or the Rwandan genocide as a global memory of injustice (Olesen, 2012). Thus, global memories tend to be local events that are commemorated outside of national boundaries and get redefined in the process (A.…”
Section: Collective Memories Of the Globally Identifiedmentioning
confidence: 99%
“…There are two types of studies on global diffusion: “top-down” research uses large data sets to ask how culture spreads (Dobbin et al 2007; Lechner and Boli 2005; Meyer 2010; Meyer et al 1997; Wejnert 2002), and “bottom-up” research uses individual cases to ask how culture enters the local context (Boellstorff 2003; Giulianotti and Robertson 2007; Jijon 2013, 2018; Levitt and Merry 2004; Merry 2006; Robertson 1995; Tsing 2005). For a long time, this bottom-up research was stuck, with scholars devising many different concepts to describe how global and local culture intersect.…”
Section: Localizing Global Culture: Advances In the “Bottom-up” Studimentioning
confidence: 99%
“…These are the “people in between” who “control the flow of information”; they are often outsiders, “open to suspicion, envy and mistrust” (Levitt and Merry 2009:449). They are experts, advisers, merchants, travelers, journalists, diplomats, guides, immigrants, or refugees (Meyer 2010:10; see also Çalişkan 2010; Gootenberg 2008; Jijon 2018; Levitt and Jaworsky 2007). Geertz (1960:229), borrowing from Wolf, called them “cultural brokers” (see also Swidler and Watkins 2017).…”
Section: Localizing Global Culture: Advances In the “Bottom-up” Studimentioning
confidence: 99%
See 1 more Smart Citation